Online Hate Speech on Social Media Platforms - Anushka Sharma; Ghanshyam Prasad Dubey; Avishi Shrivastava; Mohini Sharma; Ananya Likhar; Lokendra Sharma (International Journal of Mobile Computing Technology, 2024)
Social media is an online interactive digital platform which allows large number of group of people to connect with each other virtually, to create content and share their thoughts, information, ideas, and much more in the form of text, pictures, and videos. But sometime people share their negative view, and their message is turned into hate speech. Hate speech is of two types: online and offline. Online hate speech spreads faster than offline hate speech, spreading on platforms like Instagram, Facebook, X (formerly Twitter), etc. because when people share something, then it gets shared by their followers or friends and it reach out to millions of people and it is difficult to monitor it. This leads to rise of conflict among them based on the gender, caste, religion, culture, and country. This paper will discuss the spread of hate speech on social media platform and its identification.
Keywords: Hate speech; cyberbullying; identification; online platform; recurrent neural network (RNN); social media